Ramadan Fasting Exerts Immunomodulatory Effects: Insights from a Systematic Review - Adawi, Mohammad; Watad, Abdulla; Brown, Stav; Aazza, Khadija; Aazza, Hicham; Zouhir, Mohamed; Sharif, Kassem; Ghanayem, Khaled; Farah, Raymond; Mahagna, Hussein; Fiordoro, Stefano; Sukkar, Samir Giuseppe; et al. (Frontiers in Immunology, 2017)
Ramadan is the ninth month of the Islamic lunar calendar and is observed by Muslims as a month of fasting. All Muslim adults are expected to fast; nevertheless certain subgroups, including sick, frail subjects, and pregnant women, among others, are exempted. Ramadan fasting has been shown to impact on body systems in different manners. The influence of Ramadan fasting on immune system regulation remains elusive; however, immune system changes, such as the modulation of body response to various infectious, stressful, and other harmful events, are of great interest during fasting. In this paper, we performed an extensive systematic literature review of different scholarly databases (ISI/Web of Science, Scopus, PubMed,/MEDLINE, Google Scholar, Directory of Open Access Journals, EbscoHOST, Scirus, Science Direct, the Cochrane Library, and ProQuest), using the following key words: “fasting,” “Ramadan,” “Islam,” and “immunity.” Conclusions drawn from these findings included: (1) Ramadan fasting has been shown to only mildly influence the immune system and the alterations induced are transient, returning to basal pre-Ramadan status shortly afterward. (2) Ramadan fasting during the second trimester of pregnancy was shown to be safe and did not result in negative fetal outcomes, or maternal oxidative status alterations. (3) In cardiac patients, Ramadan fasting can have beneficial effects including lipid profile improvement and alleviation of oxidative stress. (4) In asthmatic patients as well as in patients with human immunodeficiency virus/acquired immunodeficiency syndrome and autoimmune disorders, fasting was safe. (5) In psychiatric patients, such as those suffering from schizophrenia, fasting could increase immunologic markers. (6) Fasting Muslim athletes who maintain intensive training schedule during Ramadan showed fluctuations of immunologic markers.